2007
DOI: 10.5551/jat.e486
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and Postnatal Exposure to Bisphenol A Increases Adipose Tissue Mass and Serum Cholesterol Level in Mice

Abstract: Aim: To investigate whether the perinatal and postnatal exposure of mice to bisphenol A (BPA) caused the development of obesity and/or hyperlipidemia. Methods: Pregnant mice were exposed to BPA in drinking water at concentrations of either 1 g/mL (LD group) or 10 g/mL (HD group) from gestation day 10 and throughout the lactating period. After weaning, the pups were allowed free access to drinking water containing the appropriate concentrations of BPA. The body weight, adipose tissue weight, and serum lipid lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
164
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(181 citation statements)
references
References 36 publications
11
164
3
3
Order By: Relevance
“…These results are consistent with those of other investigators who showed that perinatal BPA exposure increased body weight relative to controls (Rubin et al 2001;Miyawaki et al 2007). In addition, several investigators confirmed that BPA has a role in weight gain and the development of obesity (Newbold et al 2009;Rubin and Soto 2009;Shankar et al 2012).…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with those of other investigators who showed that perinatal BPA exposure increased body weight relative to controls (Rubin et al 2001;Miyawaki et al 2007). In addition, several investigators confirmed that BPA has a role in weight gain and the development of obesity (Newbold et al 2009;Rubin and Soto 2009;Shankar et al 2012).…”
Section: Discussionsupporting
confidence: 83%
“…This contrasts with adult studies that have linked BPA levels with cardiovascular disease and diabetes, 2 as well as mouse studies showing elevated cholesterol levels among mice with perinatal and postnatal exposure to BPA. 47 Based on these results, we consider the possibility that BPA may not have adverse effects on cardiovascular and diabetes risk. However, our cross-sectional study design may have also limited our findings, given that the adverse effects of BPA could compound over time, with health effects that manifest later in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BPA has been shown to promote adipocyte differentiation and fat accumulation, 9 as well as bind to estrogen receptors on adipocytes and inhibit the release of the hormone adiponectin. 37 While most animal studies focused on in utero exposure, Miyawaki et al 10 showed that BPA exposure during both perinatal and postnatal periods led to weight gain in mice. Additionally, long-term exposure to BPA in adult mice was shown to increase a dipose tissue mass and induce insulin resistance, hyperglycemia, and hypercholesterolemia, 38 suggesting the role of BPA in the development of obesity and cardiometabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%